Imperial Plato Text and Translation, with an Introduction and Commentary - Fowler, Ryan C. (Parmenides Publishing, 2017)
Imperial Plato presents new translations of three introductions to Plato's thought from the second half of the second century CE: Dissertation 11 of Maximus of Tyre, the Introduction to Plato by Albinus of Smyrna, and On Plato and his Teaching by Apuleius of Madaurus. These three presentations of Plato's ideas-one a Greek speech in the sophistic style of the time, another a Greek dialectic introduction with a suggested reading order for Plato's dialogues, and one a lengthy doxological study in Latin-are examples by three distinct authors using divergent methods of the assorted ways in which Plato and Platonism were understood and discussed during the revival of Hellenism and Greek Philosophy, and the period of the Roman Empire often referred to as the Second Sophistic
Description based on publisher supplied metadata and other sources
Keywords: Albinus -- Platonicus -- ca. 2.Jh. -- Introductio in Platonem; Maximus -- Tyrius -- 125-185 -- Dissertationes -- 11; Plato -- v427-v347; Apuleius -- Madaurensis -- 125-190 -- De Platone et eius dogmate; Geschichte 100-200; Albinus; Rezeption; Römisches Reich; Kommentar; Quelle